CONCEPTS IN MAGNETIC THERAPIES RELATED TO MEDICINAL BIOMAGNETISM - LITERATURE REVIEW - Aparecida Foltran, Ângela; Fernandes Ferreira, Neusa; Paes d’ Assumpção Perez, Ísis; Souza Santos, Jefferson; Mara Rambo Martini, Angela; Viapiana Bossa, Adriane (Health and Society, 2023)
Magnetism is part of one of the main pillars of physics, electromagnetism. Originally, magnetism was used by magicians and for religious purposes. In the course of history, developments in the field of magnetism have brought about great changes in societies. With industrialization and the development of electromagnetic theory, from the 19th century onwards, In the 19th century, magnetism began to take on the appearance of a science. Constant research in this area has made it possible to advance our understanding of the influences of electromagnetism on life and health. As a consequence, another area of study emerges, bioelectromagnetism, and its therapeutic implications. Medicinal Biomagnetism (BM) is an integrative and complementary therapy that aims to detect, measure and treat bioelectromagnetic changes related to illness. Through an exploratory descriptive bibliographical review, this study aims to integrate the concepts of physics and biology related to BM, proposing its integration in the list of Integrative and Complementary Practices (PICs) as a bioelectromagnetic therapy. We conclude that the theory developed by the Mexican physiotherapist and physician Dr. Isaac Goiz Durán, is based on the same principles and biophysical foundations that relate to organic biochemistry that are established by science. The practical performance of the BM continues to lack studies to clearly demonstrate how the events of diagnosis and treatment of bioelectrical, biomagnetic or bioenergetic dysfunctions are processed biophysically and biochemically and how the process of recovery of the individual’s health takes place.